Tinjauan Penyelesaian Dispute Klaim Rawat Inap Pasien Coronavirus Disease 2019 (COVID-19) di RSUD Ajibarang Tahun 2020 - Eliyah Eliyah; Aulia Ughti Ratriana (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
Dispute claim are disagreement between BPJS Kesehatan and health facilities over claims caused by coding or medical. The dispute becomes a workload for the claim submission officers and affects the hospital revenue. We found that there 66 files in dispute category at RSUD Ajibarang in April-July 2020 with a percentage of 50,8%. The purpose of this study is to analyze the causes of disputed claims for inpatient treatment based on inputs and processes, to find the solution overview. This research uses a qualitative descriptive method with case study approach and the research subjects are 4 people. The research on human resources and facilities showed relatively good conditions. Regarding the technological factor, SIMRS development is needed, the planning factor requires the creation of a special SOP to handle the COVID-19 claim dispute issue and the claim process implementation factor is seen from the flow that is in accordance with existing regulations, an introduction to the procedure for inputting COVID-19 claims is needed on INA-CBG's application. So, it can be concluded that it is necessary to prepare SOP related to disaster cases in collecting claims in the INA-CBG's application and providing human resources who have special competencies for medical recorders.